Avaliação da atividade citotóxica e indutora de apoptose da grandisina em células leucêmicas K-562 com fenótipo de resistência a fármacos - Menezes, Elizabeth Gomes Paulino (2009)
In this study the antileukemic potential of grandisin, a neolignan extracted from Piper solmsianum, was investigated against K-562 lymphocytic genealogy, which demonstrates a phenotype of resistance to new drugs. The cytotoxicity of grandisin (0.018 to 2.365 μMol) was evaluated in K-562 and in normal peripheral blood lymphocytes by using Blue of Trypan and MTT({[3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium] bromide}) methods. In the cytotoxic activity research about grandisin on K-562 cells and lymphocytes during 24 hours by the Blue of Trypan method, the grandisin got IC50 (inhibitory concentration to fifty percent) of 1.075 and 0.375 μMol to lymphocytes and K-562, respectively. After 48 hours, the cytotoxicity in normal cells remained themselves and we noticed there was an increase in IC50 leukemic cells of 0.198 μMol and 0.200 μMol in K-562 and lymphocytes, respectively. For the MTT test, results were similar to those found during the previous experiment (IC50K-562 11,98 μMol IC50lymphocytes 0,425 μMol for a period of 24 hours and IC50K-562 0,685 IC50lymphocytes 0,851 μMol for a period of 48 hours). The research about cell death mechanisms showed the treatment in K-562 cells joined to 0.036 μMol of grandisin during 24 hours, induces to an increase of cells population in G1 stage of cell cycle and it also induces to a decline of cells population in G2 stage and S, respectively. These factors also indicate that the grandisin was induced to a cell cycle standstill in G1 stage, which is proportionated to the most antileukemic agents existing. Cell death with apoptosis signs was showed by the research about these cells morphology. Moreover, the treatment of leukemic cells with 0.072, 0.036, 0.018 μMol of grandisin during 24 hours has promoted exposure of annexin V, wich is a first indicator of apoptosis. In these cells, the activity research of 3, 6 and 9 caspases and cell death mediators Bcl2 and Bax showed that cell death happens in dependent-caspase way and with balance induction between Bcl2 and Bax. Collectively, these results introduce a new model able to induce apoptosis in a leukemic cell genealogy with important features of resistance to the process of programmed cell death.